The Dry Wood - Houselander, Caryll (Book collections on Project MUSE., 2022)
"Caryll Houselander (deceased) is a woman author featured in the Catholic Women Series, which re-publishes books by previously well-known Catholic women writers that have fallen out of print. The Dry Wood is a novel set in a post-war London Docklands parish. A story about a motley group of souls mourning the loss of their parish priest. This novel is a profound meditation on the purpose of human suffering"--